Tubular Structures XIV : proceedings of the 14th International Symposium on Tubular Structures, London, UK, 12-14 September 2012 /: proceedings of the 14th International Symposium on Tubular Structures, London, UK, 12-14 September 2012. (©2012) - Unknown
No abstract available